Routing in Networks using Genetic Algorithm - Meenakshi Moza; Suresh Kumar (Institute of Advanced Engineering and Science, 2017)
With the increase in traffic, internet service providers are trying their best to provide maximum utilization of resources available. The current traffic load has to be taken into account for computation of paths in routing protocols. Network applications; require the shortest paths to be used for communication purposes. Addressing the selection of path, from a known source to destination is the basic aim of this paper. This paper proposes a method of calculating the shortest path for a network using a combination of Open shortest path first and Genetic Algorithm (OSGA). Genetic Algorithm is used in this paper for optimization of routing. It helps in enhancing the performance of the routers.